1997
DOI: 10.1046/j.1471-4159.1997.68031261.x
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Vesicle Ultrastructural Changes in the Rat Hippocampus Induced by a Combination of α‐Linolenate Deficiency and a Learning Task

Abstract: Rats fed either a safflower oil (s-linolenatedeficient) or a perilla oil (a-linolenate-sufficient) diet through two generations (Fl) showed significant differences in the brightness-discrimination learning task. In this task, correct responses were lever-pressing responses, which were reinforced with dietary pellets, and incorrect responses were those with no reinforcement. The inferior learning performance in the safflower oil group was caused mainly by the inferior ability to rectify the incorrect responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
54
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(61 citation statements)
references
References 22 publications
7
54
0
Order By: Relevance
“…As the PS and DHA contents of the aged control diet group decreased, the authors speculate that nerve activities decreased, as indicated in previous reports 5,26,29,34) . DHA contents decrease in the brain with age.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…As the PS and DHA contents of the aged control diet group decreased, the authors speculate that nerve activities decreased, as indicated in previous reports 5,26,29,34) . DHA contents decrease in the brain with age.…”
supporting
confidence: 71%
“…In animal studies, the declines in learning ability and memory have been evaluated using an 8-arm radical maze, a T maze and the light/dark discrimination test [34][35][36] . It has been shown that the loss in brain…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Tanabe et al (67) reported that Fos-positive neurons in the hippocampal CA1 increase in DHA-administered rats, and these rats showed improvement of spatial cognition. On the contrary, adult rodents with n-3 PUFA-deficient diet showed not only a decrease in the brain DHA content ranging 50% -80%, but also varieties of impaired responses in behavioral tests such as the brightness discrimination test (68), water maze test (66,69), and shock avoidance test (70). Moreover, the recovery of brain DHA level restored the spatial learning performance (71).…”
Section: Pufa and Cognitionmentioning
confidence: 99%
“…4,6,[38][39][40] The decrease in brain and retina DHA is accompanied by altered electroretinogram, decreased looking and VEP acuity, and changes in learning behaviors, including performance in maze tasks, habituation, exploratory activity in novel environments, and brightness discrimination and olfactory-based learning tasks. [3][4][5][6][7][8][41][42][43] Polydypsia and increased sterotypic (locomotor) activity have also been reported for monkeys fed diets very low in LNA. 44,45 The ability of developing animals to replace DHA with DPA indicates that the desaturase enzyme activity does not limit fatty acid desaturation and that DPA does not provide a functional substitute for DHA despite its similar carbon chain length.…”
Section: Polyunsaturated Fatty Acid Metabolismmentioning
confidence: 99%